Pertanggungjawaban Pidana Pelaku Doxing Terhadap Perempuan Korban Kekerasan Seksual Digital - Rachmanda Pepageka (Media Hukum Indonesia (MHI), 2026)
This study aims to examine the criminal liability of perpetrators of doxing against women who become victims of digital sexual violence within the framework of Indonesian positive law. Doxing refers to the act of collecting, disclosing, or disseminating an individual's personal information without consent through electronic media. Its development has transformed it from a mere violation of privacy into a form of Online Gender-Based Violence (OGBV) that disproportionately affects women. This research employs a normative legal method using statutory and conceptual approaches, with Feminist Legal Theory serving as the analytical framework. The findings reveal that although doxing has not been specifically regulated as an independent criminal offense, perpetrators may still be held criminally liable under Law Number 1 of 2024 concerning Electronic Information and Transactions, Law Number 27 of 2022 concerning Personal Data Protection, Law Number 12 of 2022 concerning Sexual Violence Crimes, and the Indonesian Criminal Code. Where doxing involves sexual content or is intended to attack the victim's sexual integrity, the provisions on Electronic-Based Sexual Violence under the Sexual Violence Crimes Law may be applied as lex specialis. Accordingly, a gender-sensitive and victim-oriented law enforcement approach is essential to ensure more effective legal protection for women who experience digital sexual violence.